Optimization and characterization of melamine urea formaldehyde (MUF) based adhesive using natural fillers for plywood - Huei, Ruey Ong (2012)
In this research, Palm Kernel Meal (PKM) and Palm Shell (PS) were studied as a filler for wood adhesive formulation and compared with present industrial filler (IF), wheat flour.Melamine Urea Formaldehyde (MUF) resin was selected as the resin for formulating the wood adhesive. The effects of natural filler on shear strength and formaldehyde emission of plywood were studied. The response surface methodology (RSM) was used to identify the optimum hot press temperature and press time for plywood process. The experimental results showed that the optimum hot press temperature and time of PKM, IF andPS were 129.5 oC; 133.7 oC; 130.7 oC and 170 sec; 159 sec;186 sec respectively. The physico-chemical interactionbetween veneer and adhesive was investigated using FourierTransform Infrared Spectroscopy (FTIR) technique. The FTIR spectrum of PKM showed blue shift which indicated that the functional groups (such as C=O, -OH and NH) become more free in the heat treatment samples. In the PKM-MUF blendbonding interactions, red shift occurred on C=O and N-H groups were observed. Red shift of C=O and N-H groups stretchingin PKM-MUF-Wood blend was observed which suggests the interaction of these functional groups occur through hydrogen bonding. In addition, PKM-Wood-MUF with different amount of PKM, the bonding interaction between C=O (PKM) with O-H and N-H groups effectively involved more as the amount of PKM increase. Plywood bonded with PKM exhibited thehighest shear strength comparitively with others. The formaldehdye emission of plywood bonded with PS was higher than PKM and IF respectively. At 13 % PKM concentration shows maximum shear strength. Experimental results showed that formaldehyde emission was minimum (environmental standard)at 18 % of PKM. This research concluded that, PKM based MUF adhesive resins exhibited potential application in production of plywood in Malaysia.